Implikasi Anarkisme Epistemologis Paul Feyerabend Terhadap Pemikiran Islam - Alamsah, Johan; Ningrum, Anggun Puspita (Universitas Islam Negeri Raden Intan Lampung, 2025)
Abstract; This research focuses on the epistemological anarchist thought of Paul Feyerabend and its implications for Islamic thought. He believes that science should not be stagnant and should not be falsified to test its truth. The author uses descriptive-analytical analysis with library research data which then results in the conclusion that in Islamic Thought Feyerabend's epistemological theory of anarchism offers an interesting perspective for understanding Islamic thought. By emphasizing plurality, ijtihad, and criticism of dogmatism, Feyerabend provides inspiration for Muslims to develop an understanding of religion that is more dynamic and relevant to the times. Keywords: Anarchism; Islamic Thought; Paul Feyerabend. Abstrak; Penelitian ini fokus pada pemikiran anarkis epistemologis Paul Feyerabend dan Implikasinya terhadap Pemikiran Islam. Ia beranggapan bahwa ilmu pengetahuan itu tidak boleh bersifat stagnan dan tidak harus difalsifikasi untuk menguji kebenarannya. Penulis menggunakan deskriptif-analitis dengan data library research yang kemudian menghasilkan simpulan bahwa dalam Pemikiran Islam teori anarkisme epistemologis Feyerabend menawarkan perspektif yang menarik untuk memahami pemikiran Islam. Dengan menekankan pluralitas, ijtihad, dan kritik terhadap dogmatisme, Feyerabend memberikan inspirasi bagi umat Islam untuk mengembangkan pemahaman agama yang lebih dinamis dan relevan dengan zaman. Kata Kunci: Anarkisme; Paul Feyerabend; Pemikiran Islam.